IDENTIFICATION OF VIBRIO BACTERIA CAUSED VIBRIOSIS ON FRESHWATER PRAWN LARVAE (Macrobrachium rosenbergii (de Man)) - Bintari, Ni Wayan Desi; Kawuri, Retno; Dalem, A. A. Gde Raka (Jurnal Biologi Udayana, 2016)
Freshwater prawn (Macrobrachium rosenbergii (de Man)) farming in Bali needs to be supported by the provisionof healthy prawn larvae. Vibriosis infection can be a limiting factor on larval production system which cause highmass mortality in larvae. Therefore a bacteriological study is very important to identify of Vibrio species whichcan cause vibriosis in freshwater prawn larvae. Screening of Vibrio bacteria carried on larval rearing water atUPT Pembenihan Dinas Kelautan dan Perikanan Provinsi Bali which located in Pesinggahan Village, Klungkung.During study, 5 Vibrio isolates can be characterized (VSP01, VSP02, VSP04, VSP05 and VSP06) which wereisolated as dominant Vibrio bacteria in larval rearing water. Koch postulate test results showed that VSP06 cancause vibriosis in freshwater prawn larvae. The result of identification by BBL Cystal™ Identification Systems andidentification book Bergeys’s Manual of Determinative Bacteriology Ninth Edition (Holt et al., 1994), BL6 wasidentified as Vibrio anguillarum.
Keywords: Freshwater prawn ((Macrobrachium rosenbergii (de Man)), Vibriosis, Vibrio anguillarum